Practical Guide to Achieve Rigor and Data Integration in Mixed Methods Research - Lorenzini, Elisiane; Osorio Galeano, Sandra Patricia; Schmidt, Catiele Raquel; Cañon Montañez, Wilson (Investigación y Educación en Enfermería, 2024)
Mixed methods research represents a dynamic approach, that combines quantitative and qualitative perspectives in the same study to answer complex questions, beyond the reach of each method used separately. This type of research is increasingly used in health sciences and in social sciences, where it is possible to identify important contributions to knowledge and the practice, derived from the characteristic integration of this approach. Nevertheless, it important to reiterate the importance of recognizing their own perspectives, methods, rigor criteria, and challenges. This work presents general aspects of the epistemological perspective of mixed methods research, describes basic and advanced designs, forms and possible integration moments of each design, as well as the rigor criteria that guide these types of studies. Graphic elements are presented to facilitate recognizing the structure of each design. Furthermore, a visual tool is introduced denominated “anatomy of mixed methods research”, which seeks to guide researchers regarding each of the key elements in the design and development of this type of research.